2021
DOI: 10.1021/acsmacrolett.1c00514
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Catalyzed Polymerization of Phenyl-Substituted Allylic Arsonium Ylides toward Nonconjugated Emissive Materials from C3/C1 Monomeric Units

Abstract: Two novel allylic arsonium ylide monomers with a phenyl (steric and electronic effect) group at different positions were synthesized and used in boron-catalyzed polymerization to produce a series of well-defined polymers, poly(2-phenylpropenylene-co-2-phenyl-propenylidene) (P2-PhAY) and poly(3phenyl-propenylene-co-3-phenyl-propenylidene) (P3-PhAY), with unusual structures but a controllable molecular weight and relatively low polydispersity. The backbone of these polymers consists of a mixture of C1 (chain gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The electron-donating effect was demonstrated to hinder the migration of boron atoms, thus influencing the insertion selectivity of the monomers. 9 These findings indicate a potential direction for regulating the insertion selectivity of the monomer by controlling the acid−base properties of active centers.…”
Section: ■ Introductionmentioning
confidence: 93%
“…The electron-donating effect was demonstrated to hinder the migration of boron atoms, thus influencing the insertion selectivity of the monomers. 9 These findings indicate a potential direction for regulating the insertion selectivity of the monomer by controlling the acid−base properties of active centers.…”
Section: ■ Introductionmentioning
confidence: 93%
“…In 2021, the same group studied the steric and electronic effects of C3 arsonium ylide on the polymer backbones. 311 Two novel allylic arsonium ylide monomers with a phenyl group at different positions were used, producing polymers with the C1/C3 mixture backbone, namely, poly(2-phenylpropenylene- co -2-phenyl-propenylidene) (P2-PhAY) and poly(3-phenyl-propenylene- co -3-phenyl-propenylidene) (P3-PhAY). DFT calculations revealed that both the steric and electronic effects guide the C1/C3 monomeric insertion.…”
Section: Polyhomologationmentioning
confidence: 99%
“…Nevertheless, less attention has been given to other physical properties of novel polyolefins with pure carbon structures such as fluorescence and crystallinity. Recently, pioneering investigations of luminous nonconjugated polyolefins, such as styrene, 44 C3 polyolefins (in which the repeat unit contains three carbon atoms), 45 polyacrylonitrile, 46 and C5 polymers (in which the repeat unit contains five carbon atoms), 47 have been reported, and all of these materials exhibit luminescence. In terms of nonconjugated luminescent polyolefins, in addition to the spatial interactions between molecular chains in the aggregated state, the distance between adjacent conjugated structures in a single chain affects the luminescence, and this phenomenon has rarely been reported.…”
Section: ■ Introductionmentioning
confidence: 99%